Pendidikan Ekologi Kritis tentang Pengelolaan Sampah: Pencegahan dan Intervensi di Eropa dan Tantangan di Asia - Firdaus, Thoriqi (PT. Pubsains Nur Cendekia, 2025)
Waste management in Europe benefits from a holistic approach and high public awareness of environmental issues, while Asia faces significant challenges in managing the current waste crisis. This research analyzes European waste prevention and intervention efforts and explores the challenges of adapting these practices in Asia. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, utilizing secondary data from journals retrieved through Google Scholar, Crossref, and Scopus. Revealing that cultural, economic, and public awareness factors significantly influence the success of waste management efforts. Effective government policies and the implementation of ecological education are critical in fostering community engagement. The most essential thing in overcoming the waste crisis is the community's ecological awareness in managing waste. Education related to critical ecology is very much needed because one ecological awareness will unite all groups' perceptions into one interest. Critical ecological education can be a solution to waste management challenges.